Wave Spectra and Shoreline Change Studies by Remote Sensing - Marghany, Maged Mahmoud (2000)
Waves play an important role in shoreline configuration. The wave pattern can induce erosion and sedimentation. Wave pattern studies using radar imagery have a potential application for coastal areas. This study investigates if the shoreline change can be modeled by wave spectra information extracted from radar images. The study area is Kuala Terengganu, located on the East Coast of Peninsular Malaysia. Mathematical modeling was carried out to extract wave spectra from radar (ERS-l and AIRSARfTOPSAR) data. The two-dimension Fast Fourier Transform (2- DFFI) was applied over selected windows on radar data. The results of the transform were wavelength and power spectra. The quasi-linear modulation model was used to map the radar wave spectra to ground-truth wave spectra to obtain the actual wave spectra. The result showed that there was a significant difference between the quasilinear model and the velocity bunching model. It suggests that the AIRSARffOPSAR data are better than ERS-l data for wave spectra investigation. This is probably because the Doppler shift effects are smaller in AIRSARffOPSAR data than in ERS-ldata. The wave spectra information was then used to predict shoreline change based on wave refraction and sediment transport. Both the wave spectra pattern derived from radar data and the wave spectra change derived from ship observations, were used to model the shoreline sedimentation and erosion pattern. Actual shoreline change was estimated from remotely sensed data by using vectorization, overlaying techniques and field measurements. The estimated shoreline change gave a rate of erosion along Chendering of 3.5 m/year between 1959 and 1994. The rate of erosion was 1 m/year along the Sultan Mahmud Airport shoreline between 1970 and 1996. The areas of erosion are similar to observations made in the field. The predicted shoreline change, from wave modeling, gave a rate of erosion from Batu Burok to Batu Rakit of less than 2 m/year and a rate of erosion to the south of Chendering of 4 m/year. The predicted and estimated result showed that the shoreline south of Chendering was always dominated by erosion throughout the year. However, overall, the beach changes along the Terengganu shoreline studied was in a state of equilibrium. The periods of erosion were balanced by periods of accretion. In conclusion, radar data (ERS-I and AIRSARffOPSAR) can be used to extract wave spectra for shoreline change modeling. Verification can be done with the assistance of other sources of data such as ship observation, ground truth data, aerial photography, other remotely sensed data, beach profiling, and sediment sampling. The combination of classical techniques, predictive modeling methods, and remote sensing technology as used in this study allows for better understanding of the interaction between ocean wave and shoreline change over a larger spatial scale and in a shorter time frame.